Critical thinking in Science education and Mathematics education: research trends of 2010-2019 (Research, Society and Development, 2020)
This research presents a systematic literature review of articles on critical thinking in Science Education and Mathematics Education. The objective is (1) to identify articles involving critical thinking in Science Education and Mathematics Education in international journals; and (2) to identify the main characteristics of these articles, in terms of: authors; years of publications; periodicals; authors' institutions; countries; citations; teaching levels; fields; the main references cited; and the number of mentions of the term critical thinking. The methodological procedures were performed according to Okoli’s 8 step guide (2015) for conducting a systemtic review and Bardin's Content Analysis (2011). The database used was the Education Resources Information Center (ERIC), from which 63 articles published in 2010-2019 were analyzed. For this, inventories were used to identify the main characteristics of the publications. The results show: a moderate number of articles (63), considering the importance the theme is given in guiding documents; articles (22%) that mention “critical thinking” without citing critical thinking references; articles (78%) that mention “critical thinking” and cite critical thinking references; and a set of articles (32%) that present critical thinking as its main focus, prioritizing the discussion of this theme. In contrast, a set of articles (43%) focused more on proposed teaching approaches than the in-depth investigation/discussion of critical thinking itself. The need for more publications with the main focus on critical thinking in Science Education and Mathematics Education is relevant, as well as research in different contexts such as the evaluation/development of students' and teachers' critical thinking.